2006
DOI: 10.1007/s00228-006-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of co-treatment with carbamazepine, amiodarone and statins on warfarin metabolism and maintenance dose

Abstract: We confirmed important interaction between carbamazepine and warfarin metabolism which can be of major clinical importance. If treatment with carbamazepine cannot be avoided, patients taking warfarin should be frequently monitored, especially when initiating or stopping carbamazepine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
0
37
1
Order By: Relevance
“…129 Several studies have demonstrated reduced warfarin dose requirements, increases in the international normalized ratio (INR), or changes in warfarin metabolite concentrations when coadministered with simvastatin. [130][131][132][133] The magnitude of effect varies, but some reports indicate up to a 30% change in INR, and 1 report showed a doubling of the number of subjects with supratherapeutic INRs. This may be specific to genetic subgroups with low functioning CYP2C9.…”
Section: Anticoagulants Warfarinmentioning
confidence: 99%
See 1 more Smart Citation
“…129 Several studies have demonstrated reduced warfarin dose requirements, increases in the international normalized ratio (INR), or changes in warfarin metabolite concentrations when coadministered with simvastatin. [130][131][132][133] The magnitude of effect varies, but some reports indicate up to a 30% change in INR, and 1 report showed a doubling of the number of subjects with supratherapeutic INRs. This may be specific to genetic subgroups with low functioning CYP2C9.…”
Section: Anticoagulants Warfarinmentioning
confidence: 99%
“…140 One study indicated that lovastatin and simvastatin affected warfarin metabolite concentrations. 131 There have been several investigations into a potential rosuvastatinwarfarin interaction. Two studies have shown a significant increase in INR, whereas 1 study did not.…”
Section: Anticoagulants Warfarinmentioning
confidence: 99%
“…Therefore, the present studies might also help explain some of the drug-drug interactions that have been observed be- Marker protein was prestained with fluorescent dye having an emission maximum at 680 nm (red), whereas the CYP4F2 antibody was conjugated with fluorophore IR800, which emits between 800 and 900 nm (green). tween warfarin and numerous statins (Hickmott et al, 2003;Andrus, 2004;Herman et al, 2006), which provoke an increase in INR and necessitate a decrease in warfarin dose. We speculate that up-regulation of CYP4F2, secondary to statin intake, might be expected to result in an increase in VK1 metabolism, reducing available levels of VK1 and lowering the requirement for warfarin.…”
Section: Cyp4f2 Is a Vitamin K 1 Mono-oxidase 1341mentioning
confidence: 99%
“…Lovastatin decreases accumulated plasma levels of very long-chain fatty acids (Singh et al, 1998), possibly by up-regulating CYP4F2. Of course, although statin-induced inhibition of warfarin metabolism through an interaction with either CYP2C9 or CYP3A4 almost certainly contributes to an increase in patient INR in specific cases (Hickmott et al, 2003), this mechanism alone does not adequately explain the full range of statinwarfarin drug interactions, based on available clinical data (Hickmott et al, 2003;Herman et al, 2006). Finally, based on the current studies, we have modified the pathway view of the vitamin K cycle to include a role for CYP4F2 in "siphoning off" excess vitamin K 1 .…”
Section: Cyp4f2 Is a Vitamin K 1 Mono-oxidase 1341mentioning
confidence: 99%
“…Hence, caution is required when comparing studies using different but apparently selective probes.Third, in addition to drugs with only Level B evidence, the classification of some drugs with Level A evidence requires subjective decisions. For example, the inhibition of CYP2C9 by amiodarone has Level A evidence with an effect at the boundary between moderate and weak inhibition [27][28][29]. Likewise, when only changes in urinary or plasma metabolite ratios are available (as is the case with many older studies for CYP2D6 and CYP2C19 substrates), interactions must be assessed by comparison with other perpetrators for which both metabolite ratios and AUC or clearance data using a recommended probe are reported.…”
Section: Cyp Inhibitorsmentioning
confidence: 99%